Implementing neoadjuvant endocrine strategies in ER-positive, HER2-negative breast cancer. Issue 4 (3rd April 2017) - Matikas, Alexios; Foukakis, Theodoros; Michalakis, Ilias; Georgoulias, Vassilis
ABSTRACT: Introduction : Although neoadjuvant chemotherapy has been widely adopted as it increases breast conservation rates, permits the in vivo testing of the activity of chemotherapeutics and offers the opportunity to conduct translational research based on longitudinal assessments of tumor tissue, neoadjuvant endocrine therapy has been met with skepticism owing to slow regression rates and a low chance for pathologic remission. Areas covered : Herein, the results of clinical trials comparing different endocrine agents as neoadjuvant treatment, endocrine therapy with chemotherapy, treatment duration, novel combinations and putative biomarkers are reviewed, with the aim to better understand the current and future role of this modality in clinical practice. Expert commentary : Available evidence clearly indicates that, in properly selected patients, short-term outcomes do not differ compared to chemotherapy. In addition, the realization that its effects at the cellular level occur shortly after its initiation and have important prognostic implications, could serve as a tool for the early identification of non-responders. Ongoing trials which integrate novel agents in addition to endocrine therapies will help guide treatment decisions and may establish neoadjuvant endocrine therapy as a standard of care for well-defined patient subgroups.